2023
DOI: 10.1177/15589250231177448
|View full text |Cite
|
Sign up to set email alerts
|

Review on development and application of 4D-printing technology in smart textiles

Abstract: 4D printed products can change shape under external stimulation, and the deformation design of material and structure is directly built into the material, which simplifies the manufacturing process from design concept to physical object and allows the object to be automatically assembled and conformed, realizing the integration of product design, manufacturing, and assembly. In recent years, 4D printing technology has also received widespread attention in the smart textile industry. This paper aims to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Applications of 4D printing have been found in areas such as soft robots and actuators [3,4], biomedical engineering [5,6], electronic * Author to whom any correspondence should be addressed. devices [7], textiles [8,9], metamaterials [10][11][12] and others. Detailed reviews on 4D printing can be found in [1,2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of 4D printing have been found in areas such as soft robots and actuators [3,4], biomedical engineering [5,6], electronic * Author to whom any correspondence should be addressed. devices [7], textiles [8,9], metamaterials [10][11][12] and others. Detailed reviews on 4D printing can be found in [1,2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…smart textile [35][36][37], self-folding packaging [38][39][40][41][42][43][44], wearable devices [45][46][47], and soft robotics [48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, 3D printing technology is employed in various medical applications, namely, medical imaging, dental restoration, pharmaceutical products, medical prostheses and implants, skin engineering, and stem cell based organ printing . Various 3D printing techniques, namely, material extrusion (MEX) or fused deposition modeling (FDM), stereolithography (SLA), selective laser melting (SLM), powder bed fusion, direct metal laser sintering (DMLS), and direct light processing (DLP), are commonly employed in the medical field. , …”
Section: Introductionmentioning
confidence: 99%
“…6 Various 3D printing techniques, namely, material extrusion (MEX) or fused deposition modeling (FDM), stereolithography (SLA), selective laser melting (SLM), powder bed fusion, direct metal laser sintering (DMLS), and direct light processing (DLP), are commonly employed in the medical field. 7,8 Among these techniques, the salient features of cost effectiveness, simple methodology, defect free product, and minimal postprocessing make the significance of MEX fascinating, especially in the 3D printing of thermoplastic materials. 9 The working principle of MEX involves the extrusion of a thermoplastic filament through a tiny nozzle by heating beyond its melting point followed by their feeding into a 3D printer to facilitate its layer by layer construction to yield a desired product.…”
Section: Introductionmentioning
confidence: 99%